Impact of heat treatment on the lifetime of wire-bonded power modules. (November 2021) - Brandelero, J.; Pichon, P.; Legros, M.
Abstract: Wire bondings in power modules are one of the weakest links in packaging, often causing an entire power module to fail. Thermo-mechanical stresses in the wire bonds related to CTE mismatch induce cracks that propagate in a region close to the bonding interface. In this paper, Scanning Electron Microscope (SEM) analysis after a bonding process clearly shows small grains and a different texture close to the interface of the wire and the die metallization. In order to improve the reliability of wire bonds, heat treatment after power module manufacturing is proposed. Heat treatment has a positive effect on the bonding region by increasing the grain size, reducing the dislocation density and merging the grains of the wire and the metallization. Furthermore, power cycling has been shown to increase the lifetime of the heat-treated power modules compared to a control comprising the same non-treated (as-delivered) IGBT power modules. Highlights: Heat treatment after power module manufacturing increased power module lifetime. First wire bond lift-off occurs later for the treated dies The local misorientation significantly decreases on bonding after thermal treatment The string of aluminium oxide particles is more dispersed on thermal treated dies